2022
DOI: 10.1002/advs.202104703
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Metal‐Free Perovskites for Piezoelectric Applications

Abstract: Metal‐halide perovskites have emerged as versatile materials for various electronic and optoelectronic devices such as diodes, solar cells, photodetectors, and sensors due to their interesting properties of high absorption coefficient in the visible regime, tunable bandgap, and high power conversion efficiency. Recently, metal‐free organic perovskites have also emerged as a particular class of perovskites materials for piezoelectric applications. This broadens the chemical variety of perovskite structures with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 149 publications
0
26
0
Order By: Relevance
“…The high temperature of weight loss suggests that the PAZE-NH 4 X 3 •H 2 O constructed with hydrogen bonds would be comparable to the traditional MHPs of MAPbI 3 (348 °C) and FAPbI 3 (363 °C) consisting of coordination bonds. [16][17][18][19][20][21][22][23][24][25][26][27] Then, scanning electron microscope (SEM) and energy-dispersive spectrometric (EDS) are further utilized to study their morphology properties and components difference in film. [12] The density functional theory (DFT) simulation is applied to explore the inherent properties of PAZE-NH 4 X 3 •H 2 O with different halide components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high temperature of weight loss suggests that the PAZE-NH 4 X 3 •H 2 O constructed with hydrogen bonds would be comparable to the traditional MHPs of MAPbI 3 (348 °C) and FAPbI 3 (363 °C) consisting of coordination bonds. [16][17][18][19][20][21][22][23][24][25][26][27] Then, scanning electron microscope (SEM) and energy-dispersive spectrometric (EDS) are further utilized to study their morphology properties and components difference in film. [12] The density functional theory (DFT) simulation is applied to explore the inherent properties of PAZE-NH 4 X 3 •H 2 O with different halide components.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Subsequently, their photoelectric, ferroelectric and mechanical properties were systematically explored as well. [19][20][21] Recently, Cui et al firstly expanded them into X-ray detection, and studied the function of hydrogen bonds in the metal-free perovskites of DABCO-NH 4 X 3 with different halide anions. [12] It is found that hydrogen bonding influenced the charge transport mobilities, and the structural stiffness of metal-free perovskites because of the changed crystal packing behaviors, which drove molecular selfassembly to co-crystals.…”
Section: Introductionmentioning
confidence: 99%
“…(3) The phase boundary’s slope in the phase diagram is pivotal for the phase stability under transition. The MPB phase stability in a wider temperature span is provided by composition modulating . In order to design polar metal-free perovskite series, quasi-spherical and momentum matching theories should be exerted.…”
Section: Introductionmentioning
confidence: 99%
“…(c) Schematic illustration of the metal-free MDABCO-NH 4 X 3 perovskite. [Reproduced with permission from ref . Copyright 2022, Wiley–VCH.]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation